1984
DOI: 10.1093/oxfordjournals.jbchem.a134750
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Size and Shape of β-Connectin, an Elastic Protein of Striated Muscle1

Abstract: Connectin is an elastic protein of vertebrate striated muscle, and consists of doublet components, alpha and beta (also called titins 1 and 2). In the present study, beta-connectin isolated in the native state was investigated in order to characterize its molecular size and shape. The molecular weight was approximately 2.1 X 10(6) (SDS gel electrophoresis) or 2.7 X 10(6) (sedimentation equilibrium). The sedimentation coefficient (SO20, w) was 17S in 0.1 M phosphate buffer, pH 7.0. The intrinsic viscosity measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 0 publications
3
70
0
Order By: Relevance
“…In 1981, having conducted a comparative study of electrophoretic mobility, amino acid composition, and localization in myofibrils of titin and connectin, Maruyama and coauthors showed that the major high molecular weight component of connectin was identical with that of titin (Maruyama et al 1981). Using crosslinked myosin heavy chains as standards, and 1.8-3.0% polyacrylamide tube gels prepared according to Weber and Osborn (1969), the authors showed that the molecular weights of α-connectin (corresponding to intact molecules of titin-1) and β-connectin (corresponding to proteolytic fragments of T1 -T2) This article is part of a Special Issue on 'Titin and its Binding Proteins in Striated Muscles' edited by Amy Li and Cristobal G. dos Remedios. of breast muscle of the chicken were 2.8 × 10 6 and 2.1 × 10 6 , respectively (Maruyama et al 1984) (Table 1, Reference 2).…”
Section: History Of the Discovery And Study Of Titin/connectin By Sdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1981, having conducted a comparative study of electrophoretic mobility, amino acid composition, and localization in myofibrils of titin and connectin, Maruyama and coauthors showed that the major high molecular weight component of connectin was identical with that of titin (Maruyama et al 1981). Using crosslinked myosin heavy chains as standards, and 1.8-3.0% polyacrylamide tube gels prepared according to Weber and Osborn (1969), the authors showed that the molecular weights of α-connectin (corresponding to intact molecules of titin-1) and β-connectin (corresponding to proteolytic fragments of T1 -T2) This article is part of a Special Issue on 'Titin and its Binding Proteins in Striated Muscles' edited by Amy Li and Cristobal G. dos Remedios. of breast muscle of the chicken were 2.8 × 10 6 and 2.1 × 10 6 , respectively (Maruyama et al 1984) (Table 1, Reference 2).…”
Section: History Of the Discovery And Study Of Titin/connectin By Sdsmentioning
confidence: 99%
“…The results obtained were impressive. The NT bands were 3230-3730 kDa, compared to the N2A, N2BA, N2B and T2 bands (Mr ∼2.1-2.8 × 10 6 ) ( Table 1, Reference 16), that corresponded to a set of values for T1 (α-connectin) and T2 (β-connectin) (Maruyama et al 1984;Wang et al 1991;Granzier and Wang 1993). Similar data were obtained for vertical agarose-strengthened 1.9% polyacrylamide gels (14.5 × 16.0 × 0.15 cm).…”
Section: Electrophoretic Detection Of Titin Isoformsmentioning
confidence: 99%
“…Among these associated proteins is the giant muscle protein titinkonnectin ("3 MDa; Maruyama et al, 1984), which spans the entire length of the thick filament and extends into the I-band and Z-disk (Furst et al, 1988;Vinkemeyer et al, 1993), and for which the function of a molecular ruler for the assembly of the thick filament has been proposed (Whiting et al, 1989). Smaller thick-filainent-associated proteins include the myosin-binding proteins C (MyBP-C) and H. The latter were discovcrcd by Offer and co-workers (Offer et al, 1973) as copurirying contaminants in myosin preparations.…”
mentioning
confidence: 99%
“…It has been shown that the faster moving band (TII) corresponds to a breakdown product of the intact molecule (TI) [91,129,141,2591. Only TI1 can be isolated under native conditions, the most effective method being that developed by Trinick et al [238] with some refinements [155].…”
Section: Titin An Extensible Integrator Of the Sarcomerementioning
confidence: 99%
“…In solution, titin TI1 exhibits abundant /3-sheet structure with no detectable a-helix [143, 1581. Improvements in sample preparation for electron microscopy, beyond those used earlier [141,238, 2601, led to a clear visualization of the titin molecule (TII) and to a more accurate determination of its in vitro length [155]. Titin TI1 appears as an extended rod, 900 nm long and 3 -4 nm in diameter, with a globular head structure at one end (Fig.…”
mentioning
confidence: 99%